Ambition meets reality: lessons from the taro boom in Nicaragua. Issue 1 (12th March 2018) - Donovan, Jason; Poole, Nigel; Poe, Keith; Herrera-Arauz, Ingrid
Abstract : Purpose: Between 2006 and 2011, Nicaragua shipped an average of US9.4 million per year of smallholder-produced fresh taro ( Colocasia esculenta ) to the USA; however, by 2016, the US market for Nicaraguan taro had effectively collapsed. The purpose of this paper is to analyze the short-lived taro boom from the perspective of complex adaptive systems, showing how shocks, interactions between value chain actors, and lack of adaptive capacity among chain actors together contributed to the collapse of the chain. Design/methodology/approach: Primary data were collected from businesses and smallholders in 2010 and 2016 to understand the actors involved, their business relations, and the benefits and setbacks they experienced along the way. Findings: The results show the capacity of better-off smallholders to engage in a demanding market, but also the struggles faced by more vulnerable smallholders to build new production systems and respond to internal and external shocks. Local businesses were generally unprepared for the uncertainties inherent in fresh horticultural trade or for engagement with distant buyers. Research limitations/implications: Existing guides and tools for designing value chain interventions will benefit from greater attention to the circumstances of local actors and the challenges of building productive inter-business relations under higher levels of risk and uncertainty. Originality/value: This case serves as a wake-up call for practitioners, donors, researchers, and the private sector on how to identify market opportunities and the design of more robust strategies to respond to them.